The presence of the environment in the works of potter Dylan Beck (Al-Academy, 2025)
The research (The presence of the environment in the works of the potter (Dylan Beck)) is concerned with studying the relationship between the natural environment and man and its reflection in artistic productions. The research is divided into four chapters. The first chapter includes a presentation of the research problem, which is summarized in the question of how the presence of the environment is represented in the ceramic productions of the potter (Dylan Beck). The aim of the research is to identify the presence of the environment in the works of the potter (Dylan Beck). The research is determined by studying the representations of the natural environment in the works of the potter (Dylan Beck) and the treatments adopted in the ceramic productions. The second chapter includes the theoretical framework, which includes three topics. The first is concerned with the concept of the environment, while the second deals with the concept of beauty, and the third topic deals with the autobiography of the potter. The third chapter deals with the research procedures, which consisted of the research community consisting of (40) ceramic works, and the research sample, which included (4) ceramic works that were chosen intentionally. The fourth chapter includes the results and conclusions of the research, and then the sources and references